EUROVISCO Guidelines for the Design and Conduct of Clinical Trials Assessing the Disease-Modifying Effect of Knee Viscosupplementation. (January 2020) - Henrotin, Yves; Chevalier, Xavier; Raman, Raghu; Richette, Pascal; Montfort, Jordi; Jerosch, Jörg; Baron, Dominique; Bard, Hervé; Carrillon, Yannick; Migliore, Alberto; Conrozier, Thierry
Objectives: Hyaluronic acid viscosupplementation is a commonly used intra-articular treatment for osteoarthritis (OA). Some recent preclinical and clinical trials have demonstrated a potential for its disease-modifying effects. The goal of this expert opinion, consensus-driven exercise is to provide guidelines for the design and conduct of clinical trials assessing the disease-modifying effect of viscosupplementation in the knee. Methods: The EUROVISCO group constitutes 10 members who had expertise in clinical research methodology in the field of OA and viscosupplementation. They initially drafted issues through an iterative process and had to vote on their degree of agreement on these recommendations. The scores were pooled to generate a median agreement score for each recommendation. Results: The document includes 31 recommendations regarding study population, imaging, clinical and biological assessment of disease-modifying effects of viscosupplementation. Agreements were reached on some recommendations. In particular, the experts reached unanimous agreement on double-blind study design, imaging primary outcomes, time interval between 2 radiographs, x-ray procedure standardization, and the combined use of imaging and biological markers. The group did not recommend the use of ultrasonography, computed tomography (CT) scan and CT arthrography as a tool for OA diagnosis or to assess progression over time. Conclusion: In summary, the working group identified 31 recommendations that represent the current best practices regarding clinical trials that target the assessment of viscosupplementation disease-modifying effects in patients with knee OA. These recommendations integrate new imaging technologies and soluble biomarkers.